The effects of vibration-reducing gloves on finger vibration - Welcome, Daniel E.; Dong, Ren G.; Xu, Xueyan S.; Warren, Christopher; McDowell, Thomas W. (International journal of industrial ergonomics, 2014)
Vibration-reducing (VR) gloves have been used to reduce the hand-transmitted vibration exposures from machines and powered hand tools but their effectiveness remains unclear, especially for finger protection. The objectives of this study are to determine whether VR gloves can attenuate the vibration transmitted to the fingers and to enhance the understanding of the mechanisms of how these gloves work. Seven adult male subjects participated in the experiment. The fixed factors evaluated include hand force (four levels), glove condition (gel-filled, air bladder, no gloves), and location of the finger vibration measurement. A 3-D laser vibrometer was used to measure the vibrations on the fingers with and without wearing a glove on a 3-D hand-arm vibration test system. This study finds that the effect of VR gloves on the finger vibration depends on not only the gloves but also their influence on the distribution of the finger contact stiffness and the grip effort. As a result, the gloves increase the vibration in the fingertip area but marginally reduce the vibration in the proximal area at some frequencies below 100Hz. On average, the gloves reduce the vibration of the entire fingers by less than 3% at frequencies below 80Hz but increase at frequencies from 80 to 400Hz. At higher frequencies, the gel-filled glove is more effective at reducing the finger vibration than the air bladder-filled glove. The implications of these findings are discussed. Prolonged, intensive exposure to hand-transmitted vibration can cause hand-arm vibration syndrome. Vibration-reducing gloves have been used as an alternative approach to reduce the vibration exposure. However, their effectiveness for reducing finger-transmitted vibrations remains unclear. This study enhanced the understanding of the glove effects on finger vibration and provided useful information on the effectiveness of typical VR gloves at reducing the vibration transmitted to the fingers. The new results and knowledge can be used to help select appropriate gloves for the operations of powered hand tools, to help perform risk assessment of the vibration exposure, and to help design better VR gloves. •The 3D transmissibility of vibration-reducing (VR) glove fingers was investigated.•A 3D laser vibrometer was used to measure the transmissibility on a 3D test system.•The tested gloves do not substantially reduce vibrations transmitted to fingers.•The results ehanced the understanding of the mechanisms of VR gloves.